Effect of Feeding Different Levels of Nigella sativa Seeds (Black Cumin) on Performance, Blood Constituents and Carcass Characteristics of Broiler Chicks - AL-Beitawi, N.; El-Ghousein, S.S. (International Journal of Poultry Science, 2008)
The effect feeding of different levels of crushed and uncrushed Nigella sativa seeds (NSS) on growth performance, blood constituents and carcass characteristics of Lohman broiler chicks was studied. An experiment with 900 day old chicks was conducted from one to 49 d of age at the poultry farm of Jordan University of Science and Technology. There were 9 dietary treatment groups: control (C), 1.5%, 2.0%, 2.5%, and 3.0%) crushed or uncrushed Nigella sativa seeds (C, T1, T2, T3, T4, T5, T6, T7 and T8) respectively. Results showed that chicks fed 1.5% crushed NSS had the higher (P < 0.05) live body weight (LBW), body weight gain (BWG) and the better (P < 0.05) feed conversion ratio (FCR). Feeding ration contains 3.0% crushed and uncrushed Nigella sativa seeds reduced (P < 0.05) plasma cholesterol and triglycerides concentration, meanwhile 3.0% crushed and uncrushed NSS increase (P < 0.05) plasma HDL level. Chicks fed 2.0% crushed NSS and control rations had the higher (P < 0.05) Total plasma protein, while, chicks fed 2.0% uncrushed NSS and control rations had the higher (P < 0.05) plasma albumin and globulin concentration. The inclusion of different levels of crushed and uncrushed Nigella sativa seeds failed to improve (P < 0.05) any of the carcass characteristics parameters.